La plateforme d’autoédition Librinova au prisme de la reconfiguration de l’intermédiation littéraire - Sylvie BOSSER (Tic & Société)
For a little less than a decade, self-publishing platforms for fiction have come to occupy a central position in the book industry. In a context of socioeconomic and cultural changes, they reflect a reconfiguration of the auctorial space, under the banner of “independence”, while also acting as traditional intermediaries, i.e. as publishers. This text looks into Librinova, the only platform to date to act as a literary agent, as publishers can use it as a test bed to evaluate manuscripts they feel unsure about. In this perspective, we will analyze the self-publishing services offered by Librinova, together with its brokerage model, in a context of increasing industrialization and marketization of symbolic goods.